2015
DOI: 10.18826/ijsets.48331
|View full text |Cite
|
Sign up to set email alerts
|

FARKLI DİNLENME ARALIKLARINDA YAPILAN ANAEROBİK İNTERVALl ANTRENMANIN, AEROBİK KAPASİTE, ANAEROBİK EŞİK VE KAN PARAMETRELERİ ÜZERİNE ETKİLERİ

Abstract: ÖzetAim: This research is to determine the effects of extensive and intensive interval training practiced in different rest interval and in the same intensity on VO 2max and anaerobic threshold and on blood parameters. Material and Methods: 20 male subjects, between 18-22 ages, are participated in the study. They are randomly separated two groups. One of them (n=10) did intensive interval training (IIT), the other one (n=10) did extensive interval training (EIT). EI and II training were applied to participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…When the literature was examined, studies similar to ours were found. While (17) stated the positive results of aerobic, anaerobic and combined technique training in their study, stated in their study that aerobic training makes significant contributions to anaerobic power outputs (18). Similarly, expressed the anaerobic effects of aerobic exercises in their study (19).…”
Section: Discussionmentioning
confidence: 94%
“…When the literature was examined, studies similar to ours were found. While (17) stated the positive results of aerobic, anaerobic and combined technique training in their study, stated in their study that aerobic training makes significant contributions to anaerobic power outputs (18). Similarly, expressed the anaerobic effects of aerobic exercises in their study (19).…”
Section: Discussionmentioning
confidence: 94%
“…Minerals and elements are important components of normal physiological behavior of the body as well as important tasks for adaptation to exercise. Minerals and elements are inorganic micronutrients found in a variety of plant and animal foods [4,5]. It is related to exercise and athletic performance, such as micronutrients, energy storage / use, protein metabolism, inflammation, oxygen transport, heart rhythms, bone metabolism, and immune function, involving hundreds of biological processes.…”
Section: Inroductionmentioning
confidence: 99%